Genetic polymorphism and their contribution to cancer susceptibility - Conforti-Froes Nívea; El-Zein Randa; Au William (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
Since the majority of chemical carcinogens are not capable of causing hazardous effects per se, the metabolism of these compounds is a crucial part of the initial host response to the environmental exposure. Disturbances in the balance between activation and detoxification may thus explain the individual variations in responses to exposures to carcinogens. The amount of the ultimate carcinogen produced depends on the action of competing activation and detoxification pathways involving cytochrome P450 and glutathione-S-transferases enzymes.